Development and exploration of refractory high entropy alloys—A review - Senkov, Oleg N.; Miracle, Daniel B.; Chaput, Kevin J.; Couzinie, Jean-Philippe (Journal of materials research, 2018)
Open literature publications, in the period from 2010 to the end of January 2018, on refractory high entropy alloys (RHEAs) and refractory complex concentrated alloys (RCCAs) are reviewed. While RHEAs, by original definition, are alloys consisting of five or more principal elements with the concentration of each of these elements between 5 and 35 at.%, RCCAs can contain three or more principal elements and the element concentration can be greater than 35%. The 151 reported RHEAs/RCCAs are analyzed based on their composition, processing methods, microstructures, and phases. Mechanical properties, strengthening and deformation mechanisms, oxidation, and corrosion behavior, as well as tribology, of RHEA/RCCAs are summarized. Unique properties of some of these alloys make them promising candidates for high temperature applications beyond Ni-based superalloys and/or conventional refractory alloys. Methods of development and exploration, future directions of research and development, and potential applications of RHEAs are discussed.